Ye dua et sev - Gilbert, Elizabeth, 1969- (Istanbul : Pegasus, 2010)
Elizabeth Gilbert recounts the experiences she had on her year-long journey around the world, and shares how her trip helped her deal with her divorce and the depression that threatened to end her career and her happiness.
Adult
Keywords: Gilbert, Elizabeth, -- 1969- -- Travel; Gilbert, Elizabeth, -- 1969- -- Travel; Travel writers -- United States; American authors; Travel writers